2016
DOI: 10.1038/gt.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus-mediated expression of myostatin propeptide improves the growth of skeletal muscle and attenuates hyperglycemia in db/db mice

Abstract: Inhibition of myostatin, a negative growth modulator for muscle, can functionally enhance muscle mass and improve glucose and fat metabolism in myostatin propeptide (MPRO) transgenic mice. This study was to investigate whether myostatin inhibition by adeno-associated virus (AAV)-mediated gene delivery of MPRO could improve muscle mass and achieve therapeutic effects on glucose regulation and lipid metabolism in the db/db mice and the mechanisms involved in that process. Eight-week-old male db/db mice were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…However, our models of muscle weakness differ from the mdx mouse in that muscles were neither dystrophic nor markedly inflammatory in huRANKLTg + nor Pparb -/mice. Consistent with our data, improving glucose entry into muscle through insulin sensitivity has been shown to improve muscle strength in 2 different mouse models of aging and type 2 diabetes (Db/Db) (28,29).…”
Section: Denosumab Improves Muscle Mass and Strength In Postmenopausasupporting
confidence: 88%
“…However, our models of muscle weakness differ from the mdx mouse in that muscles were neither dystrophic nor markedly inflammatory in huRANKLTg + nor Pparb -/mice. Consistent with our data, improving glucose entry into muscle through insulin sensitivity has been shown to improve muscle strength in 2 different mouse models of aging and type 2 diabetes (Db/Db) (28,29).…”
Section: Denosumab Improves Muscle Mass and Strength In Postmenopausasupporting
confidence: 88%
“…Eight-week-old control and Mss51-KO mice were fed an HFD for 13 weeks and then housed in individual metabolic cages and injected with 1 μCi of 1-14 C oleic acid. 14 CO 2 was collected by continuous bubbling of the air from the metabolic cage through 1N NaOH after 15, 30, 90, 180, and 240 minutes (n = 4-5 per group). The investigator conducting the experiment was blinded to the genotypes of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic ablation or postnatal inhibition of myostatin is associated with increased muscle mass and decreased adipose tissue (7,8). Since skeletal muscle plays a major role in metabolic rate and insulin-mediated glucose clearance, several studies have investigated the effects of genetic and pharmacological inhibition of myostatin in mouse models of obesity and T2DM (9)(10)(11)(12)(13)(14). These studies found that lack of myostatin resulted in increased glucose uptake and insulin sensitivity in skeletal muscle of mice (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several attempts were made to develop therapies based on myostatin propeptide for curing muscular diseases including gene therapy, antisense oligonucleotide therapy, and application of propeptide‐Fc fusion proteins 6–12 . So far, no pharmaceuticals or therapies have been approved.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the past, several attempts were made to develop therapies based on myostatin propeptide for curing muscular diseases including gene therapy, antisense oligonucleotide therapy, and application of propeptide-Fc fusion proteins. [6][7][8][9][10][11][12] So far, no pharmaceuticals or therapies have been approved. The low efficacy of direct administration of myostatin propeptide was attributed to low stability of the protein in serum.…”
mentioning
confidence: 99%